Mutations in the fukutin-related protein gene (FKRP) cause a form of congenital muscular dystrophy with secondary laminin alpha2 deficiency and abnormal glycosylation of alpha-dystroglycan. - Brockington, M; Blake, D; Prandini, P; Brown, S; Torelli, S; Benson, M; Ponting, C; Estournet, B; Romero, N; Mercuri, E; Voit, T; Sewry, C; et al. (2001)
The congenital muscular dystrophies (CMD) are a heterogeneous group of autosomal recessive disorders presenting in infancy with muscle weakness, contractures, and dystrophic changes on skeletal-muscle biopsy. Structural brain defects, with or without mental retardation, are additional features of several CMD syndromes. Approximately 40% of patients with CMD have a primary deficiency (MDC1A) of the laminin alpha2 chain of merosin (laminin-2) due to mutations in the LAMA2 gene. In addition, a secondary deficiency of laminin alpha2 is apparent in some CMD syndromes, including MDC1B, which is mapped to chromosome 1q42, and both muscle-eye-brain disease (MEB) and Fukuyama CMD (FCMD), two forms with severe brain involvement. The FCMD gene encodes a protein of unknown function, fukutin, though sequence analysis predicts it to be a phosphoryl-ligand transferase. Here we identify the gene for a new member of the fukutin protein family (fukutin related protein [FKRP]), mapping to human chromosome 19q13.3. We report the genomic organization of the FKRP gene and its pattern of tissue expression. Mutations in the FKRP gene have been identified in seven families with CMD characterized by disease onset in the first weeks of life and a severe phenotype with inability to walk, muscle hypertrophy, marked elevation of serum creatine kinase, and normal brain structure and function. Affected individuals had a secondary deficiency of laminin alpha2 expression. In addition, they had both a marked decrease in immunostaining of muscle alpha-dystroglycan and a reduction in its molecular weight on western blot analysis. We suggest these abnormalities of alpha-dystroglycan are caused by its defective glycosylation and are integral to the pathology seen in MDC1C.